Multi-objective optimization of water distribution systems based on a real options approach. (January 2015) - Marques, João; Cunha, Maria; Savić, Dragan A.
Abstract: This paper describes a multi-objective optimization model including Real Options concepts for the design and operation of water distribution networks. This approach is explained through a case study with some possible expansion areas defined to fit different future scenarios. A multi-objective decision model with conflicting objectives is detailed. Also, environmental impacts are considered that take into account not only the life cycle carbon emissions of the different materials used during the construction of the networks but also the emissions related to energy consumption during operation. These impacts are translated by giving a cost to each tonne of carbon dioxide emitted. This work presents a new multi-objective simulated annealing algorithm linked to a hydraulic simulator to verify the hydraulic constraints, and the results are represented as points on the Pareto front. The results show that the approach can deal explicitly with conflicting objectives, with environmental impacts and with future uncertainty. Highlights: We use real options to deal with uncertainty in water distribution network evolution. Carbon emissions of water distribution systems are taken into account. A new multi-objective optimization tool based on simulated annealing is developed. A group of flexible solutions is obtained for a specific case study. The results offer flexible solution alternatives to decision makers.